Immune mechanisms in vulvodynia: key roles for mast cells and fibroblasts - Tonc, Elena; Omwanda, Gloriah K.; Tovar, Kevin Arnold; Golden, Xiu Mei Emma; Chatterjea, Devavani (Frontiers in Cellular and Infection Microbiology, 2023)
Vulvodynia is a debilitating condition characterized by painful sensitivity to touch and pressure in the vestibular tissue surrounding the vaginal opening. It is often a “diagnosis of exclusion” of idiopathic pain made in the absence of visible inflammation or injury. However, the association between increased vulvodynia risk and a history of yeast infections and skin allergies has led researchers to explore whether immune mechanisms of dysregulated inflammation might underlie the pathophysiology of this chronic pain condition. Here we synthesize epidemiological investigations, clinical biopsies and primary cell culture studies, and mechanistic insights from several pre-clinical models of vulvar pain. Taken together, these findings suggest that altered inflammatory responses of tissue fibroblasts, and other immune changes in the genital tissues, potentially driven by the accumulation of mast cells may be key to the development of chronic vulvar pain. The association of increased numbers and function of mast cells with a wide variety of chronic pain conditions lends credence to their involvement in vulvodynia pathology and underscores their potential as an immune biomarker for chronic pain. Alongside mast cells, neutrophils, macrophages, and numerous inflammatory cytokines and mediators are associated with chronic pain suggesting immune-targeted approaches including the therapeutic administration of endogenous anti-inflammatory compounds could provide much needed new ways to treat, manage and control the growing global pandemic of chronic pain.